Inflammatory Arthritis: A Newly Recognized Adverse Event of Immune Checkpoint Blockade. (2nd June 2017) - Naidoo, Jarushka; Cappelli, Laura C.; Forde, Patrick M.; Marrone, Kristen A.; Lipson, Evan J.; Hammers, Hans J.; Sharfman, William H.; Le, Dung T.; Baer, Alan N.; Shah, Ami A.; Albayda, Jemima; Manno, Rebecca L.; et al.
Abstract : This commentary summarizes current knowledge on the clinical presentation, management, and outcomes of the inflammatory arthritis which may occur as an immune‐related adverse evet of immune checkpoint inhibitor therapy. Herein, we propose a new algorithm aimed at assisting oncologists in the diagnosis and management of this immune‐related adverse event.